A descriptive analysis of medical abortion commodity availability and pricing at retail outlets in 44 countries across four regions globally. Issue 1 (1st January 2021) - Durocher, Jill; Kilfedder, Catherine; Frye, Laura J.; Winikoff, Beverly; Srinivasan, Karthik
Abstract: Pharmacies in low- and middle-income countries play an important role in increasing the availability of medical abortion to individuals for self-use. We aimed to document the costs to users of medical abortion products at outlets across geographies and understand the diversity of available products, primarily in low- and middle-income countries or in places where access to abortion is restricted. A descriptive analysis of price data was completed for identified medical abortion products at retail outlets visited in 44 countries from November 2017 to February 2018. Median prices and ranges are reported in US for mifepristone 200 mg tablets, misoprostol 200 mcg tablets, and combipacks. Misoprostol, mifepristone, and combipacks were found in 44, 19, and 16 countries, respectively. Nearly two-thirds of products (321/508) required a prescription. The median price of misoprostol was 0.63 per tablet (range 0.09–27.63) based on 304 price points. Mifepristone and combipacks had fewer price points available ( n = 59 and n = 44, respectively). Median prices were 11.78 per mifepristone tablet (range 1.77–37.83) and 11.18 per combipack (range 3.50–35.86). Overall, prices were highest in Latin America and lowest in South/Southeast Asia. Only 11.5% (7/61) of the total unique misoprostol brands were quality-assured (i.e. approved by a stringent regulatory authority or pre-qualified by the World Health Organization), compared to 25.0% (4/16) of unique combipack products. There was wide variation in product pricing and availability across settings. The infrequent availability of mifepristone and combipacks, in addition to the limited availability of quality-assured medicines and high cost of abortion medications, are important factors affecting access to high-quality abortion care.